2007
DOI: 10.1016/j.schres.2006.12.016
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of language processing in people at high genetic risk for schizophrenia

Abstract: Background-Abnormalities in language processing and the related brain structures have been reported in people with schizophrenia. It has been proposed that the brain pathways for language processing are anomalous in these individuals and form the underlying basis for the positive symptoms of the illness. If language pathway abnormalities can be detected early in people at highrisk for schizophrenia prior to the onset of symptoms, early treatment can ensue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 45 publications
2
46
1
Order By: Relevance
“…However, in our preliminary whole brain activation study (Li et al, 2007), we found that in high-risk subjects and schizophrenia patients, regions of language processing were also involved during the non-linguistic control condition. Thus in these subjects, no significantly activated brain region was found during this subtraction paradigm.…”
Section: Fmri Analysesmentioning
confidence: 63%
See 4 more Smart Citations
“…However, in our preliminary whole brain activation study (Li et al, 2007), we found that in high-risk subjects and schizophrenia patients, regions of language processing were also involved during the non-linguistic control condition. Thus in these subjects, no significantly activated brain region was found during this subtraction paradigm.…”
Section: Fmri Analysesmentioning
confidence: 63%
“…Although none of the genetically at high-risk subjects had a history of psychosis, 6 were diagnosed with DSM-IV axis II schizotypal personality disorder and four had a history of at least one episode of major depression (3 of which were in the schizotypal group). Data from 15 subjects in each group were analyzed in the preliminary voxel-based analysis study (Li et al, 2007). A total of 45 of the current 77 subjects overlap with the previous study.…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations